COMPREHENSIVE MODEL OF HEAVY METALS CONTENT AND MAGNETIC PROPERTIES OF SOIL AND SEDIMENTS OF LAKES OF KHORTYSYA RESERVE - MENSHOV, Oleksandr; HOROSHKOVA, Lidiia; HOROSHKOV, Stanislav; DINDAROGLU, Turgay (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Natural and anthropogenically modified complexes of the nature reserve fund of Khortytsya Island are subject to significant pressure from human activity, technogenic processes, and military factors. It is also important to take into account the transformations caused by the regulation of the Dnipro River’s flow, the operation of the DniproHES hydroelectric station, and the consequences of the destruction of the Kakhovka Reservoir. All these factors have led to substantial changes in the water regime and landscape structure of the area. The main objective of the proposed study is to investigate changes in natural and anthropogenic landscapes of the Khortytsya reserve through the analysis of magnetic properties and the content of toxic chemical elements (in particular, heavy metals) in the bottom sediments of desiccated lakes formed as a result of the destruction of the Kakhovka Dam, as well as in the soilr. Methods. Laboratory measurements of magnetic susceptibility were conducted using a KLY-2 kappabridge. The mass-specific magnetic susceptibility χ (10⁻⁸ m³/kg) was then calculated by normalizing the obtained values to the sample mass. The elemental composition was determined using X-ray fluorescence (XRF) analysis with the ElvaX Pro instrument, a laboratory XRF analyzer capable of detecting elements in the range from Na (11) to U (92). Results. The magnetic susceptibility values in the analyzed soil samples are extremely high (χ=97–572×10⁻⁸ m³/kg). Significant exceedances of maximum permissible concentrations were recorded for zinc (2–5 times higher), chromium (20–30 times), copper (1.1–3 times), nickel (4–10 times), and cobalt (3–4 times). These elevated values are likely associated with combustion processes, as well as anthropogenic impact, particularly industrial pollution originating from Zaporizhzhia. At the same time, the behavior of magnetic susceptibility and its correlation with heavy metal content in the bottom sediments of Khortytsya lakes demonstrates different patterns. This suggests the existence of an additional mechanism contributing to the elevated magnetic signal, related to the predominance of lithogenic material likely derived from surrounding crystalline rocks of the Ukrainian Shield. Conclusions. The bottom sediments of Khortytsya lakes represent an extremely valuable natural archive for retrospective analysis of magnetic particle formation, accumulation of heavy metals, and clastic rocks of various origins, aimed at assessing both natural and anthropogenic influences on the ecosystems of the Khortytsya reserve over the past several centuries.